2021
DOI: 10.3389/fcell.2021.664527
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Role of Oxygen Metabolism in Exercise-Induced Cardiomyocyte Regeneration

Abstract: During heart failure, the heart is unable to regenerate lost or damaged cardiomyocytes and is therefore unable to generate adequate cardiac output. Previous research has demonstrated that cardiac regeneration can be promoted by a hypoxia-related oxygen metabolic mechanism. Numerous studies have indicated that exercise plays a regulatory role in the activation of regeneration capacity in both healthy and injured adult cardiomyocytes. However, the role of oxygen metabolism in regulating exercise-induced cardiomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 192 publications
(249 reference statements)
0
5
0
Order By: Relevance
“…To investigate IR pathophysiological mechanisms and drug effects, our first aim was to extend our previous in silico hiPSC-CM model ( Forouzandehmehr et al, 2022 ) by adding a metabolic model of the SERCA pump and an oxygen dynamics model linking the cellular energetics to extracellular oxygen concentration ([O 2 ] e ). Of note, the introduced dynamic oxygen formulation takes the role of contraction ATPase rate into account as we anticipated that the significance of such inclusion would be even higher in studying IR ( Bo et al, 2021 ; Laslett et al, 1985 ; McDougal and Dewey, 2017 ). We did not include I KATP in the oxygen dynamic formulation as its impact on myocardial oxygen consumption rate has been reported insignificant in IR ( Offstad et al, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate IR pathophysiological mechanisms and drug effects, our first aim was to extend our previous in silico hiPSC-CM model ( Forouzandehmehr et al, 2022 ) by adding a metabolic model of the SERCA pump and an oxygen dynamics model linking the cellular energetics to extracellular oxygen concentration ([O 2 ] e ). Of note, the introduced dynamic oxygen formulation takes the role of contraction ATPase rate into account as we anticipated that the significance of such inclusion would be even higher in studying IR ( Bo et al, 2021 ; Laslett et al, 1985 ; McDougal and Dewey, 2017 ). We did not include I KATP in the oxygen dynamic formulation as its impact on myocardial oxygen consumption rate has been reported insignificant in IR ( Offstad et al, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…12 ). We also considered the contraction energetics by adding the myofilament ATPase rate (in mM/s) to the oxygen dynamics simulations, following the significant role of contraction in myocardial oxygen consumption reported in ischemia ( Bo et al, 2021 ; Laslett et al, 1985 ; McDougal and Dewey, 2017 ). Here, the time rate of change in [O 2 ] e is given by: where, Ω was set to 1.6, as the amount of oxygen required to generate 1 mM/s ATP is equal to 1.6 mM/s as per the complete oxidation of ATP ( Wei et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that a hypoxic niche environment may regulate signalling pathways to sustain the dedifferentiation and survival of foetal cardiovascular progenitor cells [ 131 , 132 ], whereas high oxygen concentrations coincide with the stagnation of cardiomyocyte proliferation [ 133 ]. Moderate hypoxia (SaO2 75–85%) can also bolster cell cycle activities in postnatal human cardiomyocytes [ 134 ].…”
Section: The Role Of Mitochondria In Heart Regenerationmentioning
confidence: 99%
“…Long-term systemic hypoxemia could potentially reduce mitochondrial respiration and consequent ROS production in adult cardiomyocytes, which may promote cardiomyocyte re-entry into the cell cycle, thereby stimulating the proliferation of terminally differentiated cardiomyocytes [ 119 , 136 ] ( Figure 2 ). Interestingly, exercise such as treadmill running have been shown to effectively reduce cardiomyocyte ROS accumulation and induce mitochondrial uncoupling, which coincided with heart regeneration [ 133 ]. Similarly, gradual exposure to severe systemic hypoxemia in mice resulted in the inhibition of oxidative metabolism, decreased ROS production and oxidative DNA damage, and reactivation of cardiomyocyte mitosis [ 137 ].…”
Section: The Role Of Mitochondria In Heart Regenerationmentioning
confidence: 99%
“…To explore a novel and effective treatment strategy for MI, in‐depth analysis of the relevant drug treatment mechanisms is essential. Myocardial fibrosis is the primary pathological process after MI, characterized by the proliferation of myocardial interstitial fibroblasts and excessive deposition of collagen fibers 3,4 . Therefore, clarifying the mechanism and influencing factors of myocardial fibrosis provides a new perspective for the clinical treatment of MI in the future.…”
Section: Introductionmentioning
confidence: 99%